ANALISA POTENSI KETERSEDIAAN AIR UNTUK PEMBUATAN EMBUNG DI KAMPUNG KWEEL DISTRIK ELIKOBEL KABUPATEN MERAUKE - Yosehi Mekiuw (AGRICOLA, 2017)
Water is the most important natural resource for living creatures especially human. Human needs water in every aspect of his life, for agriculture, farming, industrial even for daily uses. Availability of water resource often becomes the limitation factor, so it needs the right management for human’s life continuity. The research aimed to analized the potential of water availability for recommendation to the local government, so they can build the right reservoir for water. The research used NRECA method and the result shows that the water potential in Kweel Village is approximately 49,904.86 m3.